2001
DOI: 10.1038/sj.cdd.4400905
|View full text |Cite
|
Sign up to set email alerts
|

Human mature red blood cells express caspase-3 and caspase-8, but are devoid of mitochondrial regulators of apoptosis

Abstract: Although proteases of the caspase family are essential mediators of apoptosis in nucleated cells, in anucleate cells their presence and potential functions are almost completely unknown. Human erythrocytes are a major cell population that does not contain a cell nucleus or other organelles. However, during senescence they undergo certain morphological alterations resembling apoptosis. In the present study, we found that mature erythrocytes contain considerable amounts of caspase-3 and -8, whereas essential com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
328
5
3

Year Published

2005
2005
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 328 publications
(350 citation statements)
references
References 57 publications
9
328
5
3
Order By: Relevance
“…So we decided to reinvestigate the potential role of m-calpain in regulating PS exposure during calcium-induced death of erythrocytes. In contrast to previous suggestions based on calpain inhibitory studies, 1 we found no difference in the kinetics of PS exposure, when wild type and m-calpain-null erythrocytes were exposed to either ionomycin treatment, oxidative or osmotic stress (data not shown). Altogether these observations suggest that TG2 using its crosslinking activity influences two independent cell death processes during calcium-induced death of RBCs: it facilitates the m-calpain-dependent proteolytic cleavage by directly activating m-calpain, and in addition it accelerates the PS exposure, which appears to be independent of m-calpain.…”
contrasting
confidence: 99%
See 1 more Smart Citation
“…So we decided to reinvestigate the potential role of m-calpain in regulating PS exposure during calcium-induced death of erythrocytes. In contrast to previous suggestions based on calpain inhibitory studies, 1 we found no difference in the kinetics of PS exposure, when wild type and m-calpain-null erythrocytes were exposed to either ionomycin treatment, oxidative or osmotic stress (data not shown). Altogether these observations suggest that TG2 using its crosslinking activity influences two independent cell death processes during calcium-induced death of RBCs: it facilitates the m-calpain-dependent proteolytic cleavage by directly activating m-calpain, and in addition it accelerates the PS exposure, which appears to be independent of m-calpain.…”
contrasting
confidence: 99%
“…However, recently it has been revealed that treatment of erythrocytes with the Ca 2 þ ionophore ionomycin, 1 or their exposure to oxidative or osmotic stress, 2 situations that mimic red blood cell aging, leads to cell shrinkage, cell membrane blebbing and phosphatidylserine (PS) exposure, all typical features of apoptosis in other cell types. As macrophages are equipped with receptors recognizing PS, erythrocytes exposing PS at their cell surface will be rapidly recognized, engulfed and degraded.…”
mentioning
confidence: 99%
“…After incubation at 37°C for 7 h, the erythrocytes in positive control and control were collected for measurement of the activities of caspase-8, caspase-9 and caspase-3 and the levels of ROS and cytochrome c. After washing three times with PCS, the erythrocytes in positive control were suspended in PCS and PCS containing 100 μM of Ac-IETD-fmk or Z-LEHD-fmk, 1.40 mM of Ala, Cit or Pro, 100 μM of Ac-IETD-fmk and 1.40 mM of Ala, Cit or Pro, 100 μM of Ac-IETD-fmk and Z-LEHD-fmk, or 100 μM of Ac-IETD-fmk and Z-LEHD-fmk and 1.40 mM of Ala, Cit or Pro at a 1% hematocrit, respectively. Or, a cell-free assays were performed as described by Berg et al [43] with slight modifications. Briefly, after washing with PCS, 5 Â 10 7 erythrocytes in positive control were lysed in 100 μl of lysis buffer (Beyotime, Nantong, China) and lysis buffer containing 100 μM of Z-LEHD-fmk, 2.0 μg/ml of Anti-Cyt C [44] or 2.0 μg/ml of Anti-Cyt C and 1.40 mM of Ala, Cit or Pro, respectively.…”
Section: Erythrocyte Treatmentsmentioning
confidence: 99%
“…Oxidative stress is also associated with protein degradation [158], band 3 clustering [159], phosphatidylserine externalisation [160], activation of caspases [160][161][162], and down-regulation of glycophorins [163], some of these being recognised as biomarkers of senescence or "apoptosis". In particular phosphatidylserine externalisation signals macrophages to recognise and degrade the RBCs.…”
Section: Red Blood Cellsmentioning
confidence: 99%